Code-Mixing and Code-Switching in the Interaction with the Students of English Literature Students of HKBP Nommensen - Titin Dismayanti Tumanggor; Arsen Nahum Pasaribu; Rotua Elfrida Pangaribuan (Journal of Language Education (JoLE), 2025)
This study aims to identify the types and ways of code-mixing and code-switching used in EFL students' interactions. The qualitative descriptive method was used with the foundation of Muysken's theory and Poplack's theory. The data obtained from the podcast were 125 data, with 83 code-mixing data and 42 code-switching data. The results show 32 (39%) Insertion data, 50 (60%) Alternation data, and 1 (1%) Congruent Lexicalization data. Dominated by alternation in code-mixing, while in code switching 20 (48%) inter-sentence switching data, 4 (9%) tag switching data, and 18 (43%) intra-sentence switching data. Inter-sentence switching dominates in code-switching. The researcher found that the use of code-mixing and code-switching is influenced by the social and educational environment of EFL students. Important findings include the influence of social and educational backgrounds on their linguistic choices, especially in interactions between EFL students of HKBP Nomensen Medan majoring in English literature that form patterns of code-mixing and code-switching.